HUBUNGAN KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA PERAWAT RAWAT INAP RSUD TALUK KUANTAN KABUPATEN KUANTAN SINGINGI TAHUN 2017 - NURUL KHIKMAH HAYRANI MANIHURUK (JURNAL ILMIAH KOHESI, 2018)
The prolem at the Teluk Kuantan Singingi Hospital is there a gap between nurse job satisfaction with leadership of the headroom, nurse work motivation and nurse work compensation. If this problem is allowed continue of course will give further impact, that is decreased of hospital services quality in service delivery to the commuity. So this research was conducted with the aim to know "Relationship Leadership, Motivation And Compensation With Job Satisfaction Nurse Teluk Bayu Singingi Year 2017". This study used analytical survey approach with cross sectional design, population and sample using total population of 75 nurses at Teluk Kuantan Hospital Singingi. Data collection was done by distributing questionnaires related to this research. Data analysis using Chi-Square test with 95% confidence level (p <0.05) means existence of leadership relationship of head of room, work motivation of nurse and work compensation nurse with job satisfaction nurse. The result of this research proves that the leadership of room head (p = 0.011), nurse work motivation (p = 0.001) and nurse work compensation (p = 0.001) have relationship with nurse work satisfaction with p <0.05. Furthermore, double logistic regression analysis showed that the most dominant variable with nurse work satisfaction in Teluk Kuantan Singingi General Hospital was head of room leadership. Relationship of head of room leadership, nurse work motivation and nurse work compensation to nurse job satisfaction equal to 86,7% (overall percentage 13,3), while the rest 21,3% caused by other factor. It is suggested that the management of Teluk Kuantan Singingi Hospital should apply leadership style of consultation and participation in increasing employee job satisfaction. Besides that, Teluk Teluk Kuantan Singingi should conduct periodic job satisfaction study